Peran Etika Moral dan Akhlak dalam Kultur Makan: Studi Mini Riset pada Pengunjung Handayani Pujasera Kalimantan Kabupaten Jember - badriyah badriyah; Dewita Rahma Yuliana; Fahriza Salsabila Putri; Ivana Belda; Amelia Ayu Agustin; Fradila Cindi Riawan; Nafi' Ulya Nur; Agus Arifandi (Peneliti.net, 2023)
Islam highly upholds ethical, moral and moral values in behavior. So the author wants to discuss the importance of ethics, morals, and morals in daily behavior. The awareness to behave well towards others is very important in today's life. Many young people today do not care about ethics, morals, and morals. This study aims to empirically prove the ethics, morals and morals of visitors to